Factors impacting Kansas agricultural land values: 1986 - 2009 - Pendell, Austin (Kansas State University, 2013)
Land accounts for more than 75% of a farm operation’s total assets and thus knowledge of land values are very important to landowners. However, many other parties, including lenders, appraisers, investors, and researchers also have significant interest in land markets. Over the past few decades, land prices in Kansas have increased significantly for many different reasons. The main objective of this research is to estimate the impact of various factors on Kansas land values using a hedonic regression model. In cooperation with the Property Valuation Department (PVD) of the Kansas Department of Revenue, farmland market transactions from 1986 to 2009 were obtained for this study. Hedonic models were estimated using Ordinary Least Squares to determine the impact of interest rates, urban areas, location, parcel size, and income on nominal and real Kansas land values. The estimated nominal and real models explained 24.1% and 17.2% of the variation in land prices, respectively, and the results from this study are generally consistent with previous research. This research went further into investigating the relationship between PVD data and United States Department of Agriculture (USDA) surveyed data. Results from this study indicate that USDA surveys significantly underestimate the true market for land prices across Kansas.
Keywords: Land values; Agriculture, General (0473); Economics, Agricultural (0503)